2005
DOI: 10.1016/j.molcel.2005.04.021
|View full text |Cite
|
Sign up to set email alerts
|

HDAC6 Regulates Hsp90 Acetylation and Chaperone-Dependent Activation of Glucocorticoid Receptor

Abstract: The molecular chaperone heat shock protein 90 (Hsp90) and its accessory cochaperones function by facilitating the structural maturation and complex assembly of client proteins, including steroid hormone receptors and selected kinases. By promoting the activity and stability of these signaling proteins, Hsp90 has emerged as a critical modulator in cell signaling. Here, we present evidence that Hsp90 chaperone activity is regulated by reversible acetylation and controlled by the deacetylase HDAC6. We show that H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
781
2
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 1,005 publications
(811 citation statements)
references
References 21 publications
22
781
2
6
Order By: Relevance
“…HDAC6 can not only bind both mono and poly-ubiquitinated proteins but also promote its own mono-ubiquitination. Specific inhibition of HDAC6 activity or its downregulation by siRNA increases a-tubulin and HSP90 acetylation, which reduces cellular motility, and induces HSP90 client proteins degradation, cell growth inhibition and cell death (Bali et al, 2005;Kovacs et al, 2005). Acetylated HSP90 cannot form stable complex with client proteins and its deacetylation by HDAC6 is required to regenerate functional HSP90 (Aoyagi and Archer, 2005).…”
Section: Ros Thioredoxin and Trx Binding Protein 2 Inmentioning
confidence: 99%
See 1 more Smart Citation
“…HDAC6 can not only bind both mono and poly-ubiquitinated proteins but also promote its own mono-ubiquitination. Specific inhibition of HDAC6 activity or its downregulation by siRNA increases a-tubulin and HSP90 acetylation, which reduces cellular motility, and induces HSP90 client proteins degradation, cell growth inhibition and cell death (Bali et al, 2005;Kovacs et al, 2005). Acetylated HSP90 cannot form stable complex with client proteins and its deacetylation by HDAC6 is required to regenerate functional HSP90 (Aoyagi and Archer, 2005).…”
Section: Ros Thioredoxin and Trx Binding Protein 2 Inmentioning
confidence: 99%
“…As indicated above, this chaperone protein is essential for the stability and function of many client proteins, including steroid hormone receptors and protein kinases, that are crucial for numerous cell signaling processes and cellular homeostasis (Solit and Rosen, 2006). Recent studies have demonstrated both a direct physical interaction between HDAC6 and HSP90, and HDAC6 as a regulator of HSP90 activity, through its deacetylation (Bali et al, 2005;Kovacs et al, 2005). Considering the number of HSP90 client proteins, many molecular alterations can be anticipated as a result of HSP90 inactivation through HDAC6 inhibition by HDACi, or its downregulation by HDAC6 siRNA.…”
Section: Ros Thioredoxin and Trx Binding Protein 2 Inmentioning
confidence: 99%
“…While it is clear that acetylation and phosphorylation are important aspects of Hsp90's in vivo function, the precise role of these modifications in the chaperone cycle is not well understood. Hyperactylation of Hsp90 disrupts the binding of both client proteins and co-chaperones (Kekatpure et al, 2009;Kovacs et al, 2005;Scroggins et al, 2007;Yu et al, 2002). Regulation of Hsp90's acetylation status occurs primarily through HDAC6 which binds directly to Hsp90 (Kekatpure et al, 2009), and inhibition of HDAC6 leads to the hyperacetylation of Hsp90 (Yu et al, 2002).…”
Section: The Effect Of Phosphorylation and Acetylation On The Conformmentioning
confidence: 99%
“…Of the known substrates of HDAC6, Hsp90 may be linked with the HDAC6-mediated regulation of mitochondrial metabolic activity. Inactivation of HDAC6 leads to hyperacetylation of Hsp90 and instability of its client proteins [6,7]. Interestingly, Kang et al have found that an abundant pool of Hsp90 localizes to mitochondria in various tumor cells and regulates mitochondrial integrity [21].…”
Section: Hdac6 Regulates Mitochondrial Metabolic Activity In the Cytomentioning
confidence: 99%
“…Early studies found that HDAC6-mediated a-tubulin deacetylation destabilizes dynamic microtubules [3] and promotes an increase in cell motility [4,5]. In addition to a-tubulin, several cytoplasmic proteins including Hsp90 [6,7], cortactin [8], b-catenin [9], peroxiredoxins I and II [10], and Ku70 [11] are regulated in a HDAC6-mediated deacetylation-dependent manner. Strong ubiquitin binding activity [12,13] further adds to the multifunctionality of HDAC6, enabling the regulation of many important processes including cell migration, cell stress response to the cytotoxic accumulation of protein aggregates, and immune synapse formation [1,2].…”
Section: Introductionmentioning
confidence: 99%